Dichloroacetate stimulates changes in the mitochondrial network morphology via partial mitophagy in human SH-SY5Y neuroblastoma cells - Pajuelo-Reguera, David; Alán, Lukáš; Olejár, Tomáš; Ježek, Petr (International journal of oncology, 2015)
Dichloroacetate (DCA) is beneficial in cancer therapy because it induces apoptosis and decreases cancer growth in vitro and in vivo without affecting non-cancer cells. DCA stimulates the activity of the enzyme pyruvate dehydrogenase by inhibiting pyruvate dehydrogenase kinase. Consequently, DCA promotes oxidative phosphorylation after glycolysis. Therefore, DCA produces changes in energy metabolism that could affect the mitochondrial network and mitophagy. This investigation determined the effects of DCA treatment on mitophagy in human neuroblastoma SH-SY5Y cells. SH-SY5Y cells were cultured and distributed into 3 groups: control, NH4Cl and chloroquine. Each group was treated with DCA at 0, 5, 30 and 60 mM for 16 h. Samples were analyzed for cell viability, mtDNA copy number, mitochondrial network morphology and expression of key proteins involved in mitochondrial dynamics, such as LC3b, FIS1, OPA1, PARKIN and PINK1. In all groups, DCA caused a decrease in cell viability, an induction of autophagy in a dose-dependent manner and a decrease in Tim23, FIS1 and PARKIN protein expression, leading to profound morphological changes in the mitochondrial network resulting in shorter and more fragmented filaments. However, TFAM protein levels remained unchanged. Similarly, the mitochondrial copy number was not significantly different among the treatment groups. In conclusion, DCA induces mitophagy and remodeling of the mitochondrial network. In this remodeling, DCA induces a decrease in the expression of key proteins involved in protein degradation and mitochondrial dynamics but does not significantly affect the mtDNA density. Blocking late phase autophagy increases the effects of DCA, suggesting that autophagy protects the cell, at least partially, against DCA.
Keywords: autofagie; Neuroblastoma; variabilita počtu kopií segmentů DNA; Chloroquine; neuroblastom; Humans; DNA Copy Number Variations; lidé; Cell Survival; mitochondriální proteiny; Gene Expression Regulation, Neoplastic; DNA, Mitochondrial; Cell Line, Tumor; mitofagie; kyselina dichloroctová; chlorochin; regulace genové exprese u nádorů; Mitophagy; mitochondriální DNA; Autophagy; viabilita buněk; nádorové buněčné linie; Dichloroacetic Acid; Mitochondrial Proteins